PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LIKUIDITAS TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN INFRASTRUKTUR TAHUN 2019-2021 - Irmayani Maulina Putri; Pujianto Pujianto (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2023)
The aim of this research is to determine the influence of company size, profitability, and liquidity on audit report lag. This research uses a type of causal research with a quantitative approach. The population of this research is infrastructure companies listed on the Indonesia Stock Exchange. The sampling method used purposive sampling, obtained as many as 22 companies with 3 years of observation (2019-2021) so there were 66 samples. Data analysis was carried out using SPSS version 26. The results prov that company size has no significant effect on audit report lag, while profitability and liquidity have a significant effect on audit report lag. Meanwhile, audit report lag is influenced simultaneously by company size, profitability, and liquidity.